Nurturing Talent: The IT Academy Journey into Quality Development - Goelzer, Natalya Marjana; Possamai, Pedro Portella; Marczak, Sabrina; Móra, Michael da Costa; Callegari, Daniel Antonio (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2024: Anais do XXIII Simpósio Brasileiro de Qualidade de Software, 2024)
The IT Academy, a collaborative initiative between a multinational company named ORG and the Pontifical Catholic University of Rio Grande do Sul (PUCRS), prepares new interns for ORG through intensive training. This paper presents an experience report on the practical phase of the training program, highlighting the adoption of agile methodologies to teach software development quality through Hands-on practice. The discussion addresses the benefits of this learning environment, focusing on the development of technical and interpersonal skills. The Program promotes a culture of collaboration and teamwork, enhancing communication and cooperation skills among participants. The continuous feedback and mentorship process ensures the ongoing improvement of the development process, fostering a cohesive and productive work environment. The practice aligned with company standards increases the relevance and applicability of the acquired competencies. Key lessons learned include the effective use of quality inspection tools, time management, and the importance of continuous feedback. The program’s success suggests that its practices are replicable, contributing to developing new talent within organizations.